WHAT CAN FIGHTING TELL US ABOUT JOURNALISTIC IDENTITIES? - Pereira, Fábio Henrique (Brazilian journalism research, 2023)
ABSTRACT – In this essay we argue that journalists’ engagements, their fights, reveal, indeed, the dynamics of how their professional identities are constructed. By engaging in a struggle, the journalist seeks to state something about himself, for himself (and his profession group) and for the others (actors that participate in this public combat). The journalism fights reveal the way the professional group (or part of it) tries to manage its relationship with rival actors at the same time it expresses a public discourse about its practice, its identity. The journalism fights reveal the temporary or permanent alliance journalists establish within the professional group, as so with external actors who share the same interests. Fighting is also participating in the construction of a social problem, by converting some issues/situations specific to the professional group to a subject that interest the whole society. RESUMO – Neste ensaio, argumentamos que o engajamento dos jornalistas, suas lutas, revelam as dinâmicas de construção das identidades profissionais. O jornalista, quando se engaja em um combate, tem a intenção de dizer algo sobre si, para si (para o grupo profissional) e para os outros (atores que participam do combate público). Os combates do jornalismo revelam a forma como o grupo profissional (ou parte dele) busca gerir as relações com atores concorrentes ao mesmo tempo em que exprime um discurso público sobre sua prática, sua identidade. Os combates do jornalismo também revelam as alianças, temporárias ou permanentes, que os jornalistas estabelecem no interior do grupo, mas também com atores externos, que partilham dos mesmos interesses. Combater é também participar da construção de um problema público, por meio da conversão de certas questões/situações específicas ao grupo profissionais em um tema de interesse da sociedade. RESUMEN – En este ensayo, sostenemos que el compromiso de los periodistas, sus luchas, revelan la dinámica de construcción de sus identidades profesionales. Cuando el periodista entra en combate, él pretende decir algo sobre sí mismo, para sí mismo (para el grupo profesional) y para los demás (actores que participan en el combate público). Las luchas del periodismo revelan la forma en que el grupo profesional (o parte de él) procura gestionar las relaciones con sus competidores mientras expresa un discurso público sobre su práctica y identidad. Los combates del periodismo también revelan las alianzas, temporales o permanentes, que los periodistas establecen dentro del grupo, pero también con actores externos, que comparten los mismos intereses. Combatir es también participar en la construcción de un problema público, a través de la conversión de determinadas cuestiones/situaciones propias del colectivo profesional en un tema de interés para la sociedad.